Screening of high chitinase-producing stains from Trichoderma harzianum and conditions for enzyme production - WANG Hong-mei; JIANG Li-ke; TAO Fang; WEI Lian-ping; YUE Yong-de (浙江大学学报. 农业与生命科学版)
Trichoderma harzianum wild-type strains were implanted by N+ to produce mutagenesis. A mutant stain H-13 with higher activity of chitinase was obtained by screening the mutants with transparent zone, and analyzing chitinase activity by DNS method. Single-factor design and orthogonal test design were used for optimizing cultural conditions of chitinase production from mutant strain H-13. Single-factor experimentation showed that the media added 1.0% peptone led to highest chitinase production, and 1.0% colloidal chitin was the best media for inducing chitinase. The mutant strain showed higher enzymatic activity in this media with initial pH 5.5 for 96 h of culture. Orthogonal test showed that chitinase activity of strain H-13 could reach 731.69 U·mL-1 cultured in the optimal medium with 1.0% peptone, 0.5% colloidal chitin and initial pH 5.0 for 96 h, which was one fold increase compared to the wild strain enzyme vigor.